2020
DOI: 10.1136/rmdopen-2020-001170
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Patient Acceptable Symptom State (PASS) in psoriatic arthritis: association with disease activity and quality of life indices

Abstract: ObjectiveThe aim of this study was to evaluate the discriminant capability of the Patient Acceptable Symptom State (PASS) according to disease activity, remission/low disease activity indices and quality of life indices in patients with psoriatic arthritis (PsA).MethodsConsecutive patients with PsA were enrolled in this cross-sectional study. At each visit, the patients underwent a complete physical examination and their clinical/laboratory data were collected. Disease activity was assessed using the Disease A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…In a prospective international study of 410 patients with PsA that evaluated patient- and physician-perceived remission and LDA (measured by ‘yes/no’ questions), physicians appeared to consider patients to be in remission more often than patients did, whereas the opposite was true for LDA [ 15 ]. Similarly, a recent post hoc analysis of 223 patients with PsA showed disagreement between HCP-judged remission (measured by a ‘yes/no’ question), and patients considering themselves to be ‘well’ (measured by Patient Acceptable Symptom State, a single-question tool with potential for use as an alternative measure of disease activity in patients with PsA in clinical practice [ 16 ]) [ 17 ]. Additionally, a multicenter European study of 460 patients with PsA revealed discordance between HCP and patient global assessments of disease activity [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective international study of 410 patients with PsA that evaluated patient- and physician-perceived remission and LDA (measured by ‘yes/no’ questions), physicians appeared to consider patients to be in remission more often than patients did, whereas the opposite was true for LDA [ 15 ]. Similarly, a recent post hoc analysis of 223 patients with PsA showed disagreement between HCP-judged remission (measured by a ‘yes/no’ question), and patients considering themselves to be ‘well’ (measured by Patient Acceptable Symptom State, a single-question tool with potential for use as an alternative measure of disease activity in patients with PsA in clinical practice [ 16 ]) [ 17 ]. Additionally, a multicenter European study of 460 patients with PsA revealed discordance between HCP and patient global assessments of disease activity [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…DAPSA was calculated by adding the number of tender and swollen joints, pain on VAS, PtGA, and CRP (mg/dl) [ 17 ]. The PASS is a single question tool to evaluate the level of symptoms at which patients consider themselves well [ 9 ]. The PsAID was also assessed [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the aim of this clinical study was to look at the MDA divided into the seven cutoffs (from 1/7 to 7/7) and analyzing which domains were more frequently achieved, in particular in those not satisfying the MDA, namely from 1/7 to 4/7, in a group of PsA patients, as a “climb” towards MDA. A secondary aim was to assess the relationship between MDA, categorized into seven cutoffs, with the Patient Acceptable Symptoms State (PASS) [ 9 ], the Psoriatic Arthritis Impact of the Disease (PsAID) [ 10 ], the Disease Activity for Psoriatic Arthritis (DAPSA) [ 11 ], and the Physician Global Assessment (PhGA).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical assessment encompassed the number of tender and swollen joints (out of the 68/66 assessed joints), enthesitis, and dactylitis. Enthesitis was assessed by using the Leeds Enthesitis Index (LEI) [ 20 ], and dactylitis as present/absent, as published elsewhere [ 21 , 22 ]. Skin assessment was performed using the body surface area (BSA).…”
Section: Methodsmentioning
confidence: 99%